1897. Letermovir Salvage for Complicated Cases of Resistant CMV. (26th November 2018) - Turner, Nicholas; Strand, Andrew; Saullo, Jennifer; Arif, Sana; Maziarz, Eileen K; Grewal, Dilraj; Baker, Arthur W; Wolfe, Cameron R
Abstract: Background: Limited treatment options exist for ganciclovir-resistant CMV disease. Foscarnet can cause renal insufficiency, and maribavir has poor ocular penetration. Letermovir is approved for primary CMV prophylaxis in hematopoietic stem cell transplantation, but efficacy in treatment of CMV disease or secondary prophylaxis is not known. Methods: We analyzed data from all adult patients at a single center who initiated letermovir for treatment of CMV disease or secondary prophylaxis of CMV retinitis from November 2017 through April 2018. We described patient characteristics, extent of CMV disease, prior antiviral therapies, kinetics of CMV DNAemia, and clinical outcomes. Results: Four patients received letermovir for treatment, and one for secondary suppression, of CMV DNAemia and CMV retinitis (table). All patients had proven genotypic resistance with complications and/or clinical failure on prior antivirals. Letermovirdoses ranged from 480 mg to 720 mg daily. Three patients received concomitant CMV immune globulin and intravitreal therapy with foscarnet and/or ganciclovir. No patients developed side effects attributable to letermovir, and expected increases in tacrolimus levels occurred. All five patients demonstrated clinical and retinoscopic improvement (Figure 1), but two patients did not achieve complete resolution of DNAemia (Figure 2). Conclusion: Use of letermovir, often in combination with intravitreal therapy, was associated with sustained clinical improvement in five patients with CMV retinitis. Treatment doses of up to 720 mg were well tolerated. Despite marked improvement of ocular disease, two patients did not achieve sustained suppression of DNAemia. Disclosures: C. R. Wolfe, Merck: Scientific Advisor, Consulting fee.